A Review of Upcycle Coffee Cherry Husk (Cascara) in Kombucha Fermentation: Enhancing Bioactive Compound Potential - Helga Zefanya Wical; Clarinda Djuali; Lamsihar Alex Siregar (Soegijapranata Catholic University, 2025)
The growing concern about managing diabetes and adhering to dietary restrictions has led to the development of low-sugar, nutritious products. Kombucha, a fermented tea produced with a symbiotic culture of bacteria and yeast (SCOBY), provides essential probiotics and enzymes that aid digestion and boost the immune system. Cascara, or the dried husk of the coffee cherry, contains bioactive compounds such as quercetin, chlorogenic acid, and ferulic acid, making it valuable for managing oxidative stress, diabetes, and regulating enzymes. Combining cascara with kombucha presents an opportunity to enhance the beverage's health benefits. Generally, fermentation for 10– 14 days with 100 g/L sucrose produced an optimal balance in pH, total phenolic content (TPC), flavonoid content (TFC), and antioxidant activity. Cascara kombucha also demonstrated antibacterial effects against Staphylococcus aureus, Escherichia coli, and Salmonella enterica. This review highlights that cascara kombucha is not only a promising functional beverage but also a sustainable strategy for reducing coffee waste and improving post-harvest economic value.